An extremely prolonged second stage of labor increases maternal complications but has no adverse effect on neonatal outcomes. Issue 6 (13th March 2022) - Hagiwara, Mayumi; Nakanishi, Sayuri; Shindo, Ryosuke; Obata, Soichiro; Miyagi, Etsuko; Aoki, Shigeru
Abstract: Aim: To investigate how an extremely prolonged second stage of labor of 12 h or more affects maternal and neonatal outcomes. Material and methods: This retrospective cohort study included nulliparous, pregnant women with 37 + 0 to 41 + 6 weeks of gestation whom vaginal delivery was attempted at the Yokohama City University Medical Center between 2014 and 2018. Results: In 446 cases of the prolonged second stage of labor, there were 296 women (66%) in the 2‐ to 6‐h second stage of labor group, 112 women (25%) in the 6‐ to 12‐h group, and 38 women (8.5%) in the 12‐h or longer group. The longer the second stage of labor, the more significant was the increase in the rates of augmentation of the delivery, emergency cesarean delivery, and operative vaginal delivery. Even in the 12 h or longer group, 82% were able to have vaginal delivery. The 6‐ to 12‐h group had a significant increase in third‐ or fourth‐degree perineal lacerations compared to the 2‐ to 6‐h group (aOR 8.12 [95% CI 1.55–42.6]). Clinical chorioamnionitis was significantly increased in the 12 h or longer group (aOR 4.88 [95% CI 1.62–14.8]). In terms of neonatal outcomes, comparison between the three groups showed no significant difference. Conclusion: With an extremely prolonged second stage of labor, maternal complications involved a significant increase in severe perineal lacerations and chorioamnionitis; however, there was no increase in adverse outcomes for neonates. It was not possible to conclusively determine if the duration of the second stage is acceptable.